Regular swimming before the induction of ulcer ameliorates oxidative gastric damage in rats: The anxiolytic effect of exercise - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: To investigate the impact of exercise on ulcerogenesis. Materials and Methods: Gastric ulcer was induced in Wistar albino rats that were either kept sedentary or had swimming exercise for 6 weeks. Under anesthesia, ulcer was induced by applying acetic acid on the stomach serosa, while control rats had sham-operation. On 3rd or 10th days of ulcer induction, anxiety levels were measured and rats were decapitated for measuring serum cortisol level, while gastric tissue samples were obtained for histopathologic analysis and for determination of malondialdehyde (MDA), glutathione (GSH) levels, myeloperoxidase (MPO) activity, luminol-and lucigenin-enhanced chemiluminescence (CL) and nitric oxide (NO) levels. Results: In sedentary 3-day-ulcer group, gastric MPO activities were elevated with concomitant reductions in GSH content, while these changes were reversed in 10-day ulcer group. In exercised 3-day-ulcer group, all parameters were significantly reversed. Increased lucigenin-CL was suppressed, while NO levels were elevated by exercise. Histological analysis revealed lower lesion scores in exercised groups. Serum cortisol levels were not different among ulcer groups, but anxiety was suppressed by swimming exercise in 3-day-ulcer group. Conclusion: Regular swimming exercise ameliorated acetic acid-induced oxidative damage of stomach via inhibition of neutrophil infiltration and through anti-stress effect of exercise. Regular exercise may be considered in facilitating the healing of gastric ulcers.
Keywords: Acetic acid; Gastric ulcer; Exercise; Myeloperoxidase; Anxiety